2000
DOI: 10.1073/pnas.97.20.10978
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of senescence in human cervical carcinoma cells

Abstract: Expression of the bovine papillomavirus E2 regulatory protein in human cervical carcinoma cell lines repressed expression of the resident human papillomavirus E6 and E7 oncogenes and within a few days caused essentially all of the cells to synchronously display numerous phenotypic markers characteristic of cells undergoing replicative senescence. This process was accompanied by marked but in some cases transient alterations in the expression of cell cycle regulatory proteins and by decreased telomerase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
182
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(195 citation statements)
references
References 40 publications
11
182
1
1
Order By: Relevance
“…Whereas, we specifically target E6 by RNAi, treatment with IP10 resulted in the inhibition of both E6 and E7 expression. Yet, in contrast to studies indicating that combined E6 and E7 inhibition primarily results in senescence (Goodwin et al, 2000;Wells et al, 2000;Hall and Alexander, 2003), induction of apoptosis was reported. In addition, IP10 is likely to exert additional biological activities besides affecting E6/E7 expression.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Whereas, we specifically target E6 by RNAi, treatment with IP10 resulted in the inhibition of both E6 and E7 expression. Yet, in contrast to studies indicating that combined E6 and E7 inhibition primarily results in senescence (Goodwin et al, 2000;Wells et al, 2000;Hall and Alexander, 2003), induction of apoptosis was reported. In addition, IP10 is likely to exert additional biological activities besides affecting E6/E7 expression.…”
Section: Discussioncontrasting
confidence: 66%
“…E6 targets the PUMA/Bax Pathway M Vogt et al inhibition of E6 and E7. The combined inhibition of E6 and E7 primarily leads to growth arrest and senescence (Goodwin et al, 2000;Wells et al, 2000;Hall and Alexander, 2003), due to the release of pRb from the inhibitory influence of E7 (Psyrri et al, 2004). However, if growth arrest cannot be induced -due to the sustained inactivation of pRb-associated pathways by E7 -inhibition of E6 alone will result in Bax-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…58 HPVs interfere with both pathways through the activity of the viral E6 and E7 oncoproteins, 3 and reactivation of p53 and pRb activities after E6/E7 inhibition is linked to senescence induction. [35][36][37]57 This reconstitution of p53, as also observed under our experimental conditions, could affect exosome release as p53 can stimulate the TSAP6 and CHMP4C genes, which both enhance exosome formation by unknown mechanisms. [38][39][40][41] In line with this possibility, we found that the enhanced intracellular p53 levels on E6/E7 inhibition were linked to increased expression of both TSAP6 and CHMP4C in HeLa cells.…”
Section: Infectious Causes Of Cancersupporting
confidence: 73%
“…Our results suggest that a senescence response controlled by PML could be an important barrier to prevent the establishment of cervical carcinoma. Consistent with this idea, blocking the expression of E6 and E7 in cell lines derived from cervical carcinoma re-establishes the functions of p53 and Rb and induces senescence (Goodwin et al, 2000;Wells et al, 2000). Since PML is a critical regulator of senescence, studying the status of PML could be useful to predict the outcome of HPV infections of the cervix or the prognosis of premalignant cervical lesions.…”
Section: Discussionmentioning
confidence: 70%